Moving Through Virtual Reality Without Moving? - Riecke, Bernhard E.; Sigurdarson, Salvar; Milne, Andrew P. (Cognitive Processing, 2012)
Virtual Reality (VR) technology is increasingly used in spatial cognition research, as it offers high experimental control and interactivity in naturalistic multi-modal environments, something that is difficult to achieve in real-world settings. Even in the most sophisticated and costly VR systems people do not necessarily perceive and behave as they would in the real world. This might be related to our inability to use embodied (and thus often highly automated and effective) spatial orientation processes in VR. While real-world locomotion affords automatic and obligatory spatial updating of our self-to-surrounding relationships, such that we easily remain oriented during simple perspective changes, the same is not necessarily true in VR. This can lead to striking systematic and qualitative errors such as failures to update rotations (“Nonturner” behaviour). Here, we investigated whether rich naturalistic visual stimuli in immersive VR might be sufficient to compensate for the lack of physical motion. To this end, 24 participants performed point-to-origin tasks after visually simulated excursions along streets of varying curvature in a naturalistic virtual city. Most (21/24) participants properly updated simulated self-motions and showed only moderate regression towards mean pointing responses. 3/24 participants, however, exhibited striking “Nonturner” behaviour in that they pointed as if they did not update the visually simulated turns and their heading had not changed. This suggests that our immersive naturalistic VR stimuli were an improvement over prior optic flow stimuli, but still insufficient in eliciting obligatory spatial updating that supported correct point-to-origin responses in all participants.
Keywords: 812; Riecke; Riecke_2012; andrew-milne; iat812; iat812_spring2011; journalPaper; point-to-origin; salvar-sigurdarson; vection